2008
DOI: 10.1016/j.biopsych.2008.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Nonsynonymous Variant of DAOA with Visuospatial Ability in a Bipolar Family Sample

Abstract: BackgroundBipolar disorder and schizophrenia are hypothesized to share some genetic background.MethodsIn a two-phase study, we evaluated the effect of five promising candidate genes for psychotic disorders, DAOA, COMT, DTNBP1, NRG1, and AKT1, on bipolar spectrum disorder, psychotic disorder, and related cognitive endophenotypes in a Finnish family-based sample ascertained for bipolar disorder.ResultsIn initial screening of 362 individuals from 63 families, we found only marginal evidence for association with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Additional evidence supports the involvement of DAOA/G30 and DAO in the etiology of bipolar disorder, but none indicated any interaction between these genes 30 . DAOA thus may play an important role in the predisposition of individuals with a mixed phenotype of psychosis and mania and lead to changes in the expressed characteristics of these psychological illnesses 31 . Williams et al 32 suggested that depression is associated with greater glutamatergic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence supports the involvement of DAOA/G30 and DAO in the etiology of bipolar disorder, but none indicated any interaction between these genes 30 . DAOA thus may play an important role in the predisposition of individuals with a mixed phenotype of psychosis and mania and lead to changes in the expressed characteristics of these psychological illnesses 31 . Williams et al 32 suggested that depression is associated with greater glutamatergic function.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of these articles associated identified five genes as the most cited in the literature: CANAC1C [16][17][18][19][20][21][22][23][24] , DAOA [25][26][27][28][29][30][31][32] 22 . Some articles related the genetic polymorphism specifying the classification of TBI 8,25,27,32,35,36,39,41 , in addition to TBI and II 37 .…”
Section: Genes and Polymorphisms Associated With Demonstrationmentioning
confidence: 99%
“…Schizophrenia and bipolar mood disorders affect many families simultaneously. This theme suggests that these disorders have a shared genetic etiology at least to some extent [29]. Traditionally, search for predisposing genes, has proceeded under the presumption that schizophrenia and bipolar disorder are segregate disease entities.…”
Section: Discussionmentioning
confidence: 99%
“…It causes an arginine-to-lysine substitution at codon 30 (Arg30Lys) and might therefore be of putative functional relevance (Donohoe et al, 2007). Recently, it has been shown that the DAOA rs2391191 SNP variant is associated with a significantly lower visual memory capacity in patients with a psychotic disorder (Soronen et al, 2008). Additionally, the rs2391191 SNP variant is associated with impaired verbal memory in schizophrenia (Donohoe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%